An event-triggered mechanism to observer-based sliding mode control of fractional-order uncertain switched systems. (April 2023) - Meng, Xin; Jiang, Baoping; Karimi, Hamid Reza; Gao, Cunchen
Abstract: This paper is dealing with the problem of observer-based event-triggered sliding mode control for fractional-order uncertain switched systems with a positive order less than one. Firstly, a fractional-order state observer is designed, based on which a fractional-order integral sliding surface function is proposed. Then, utilizing the estimated observer error and sliding mode error vectors, an event-triggered condition is constructed to decide whether the current control signal should be updated or not. Besides, sufficient conditions are derived in the forms of linear matrix inequalities (LMIs) to ensure finite-time stability of the augmented closed-loop system by adopting an average dwell time approach. Thereafter, to avoid the occurrence of infinite triggers within finite time, this paper also discusses the Zeno behavior and refines the results in the previous literature. Finally, to illustrate the effectiveness and superiority of the proposed method, three numerical simulations are provided. Highlights: Introducing a fractional-order observer to the event-triggered SMC problem of uncertain switched systems. A corrected result is presented to avoid the Zeno behavior for the fractional-order switched systems under the presented event-triggered condition. Strict LMIs are derived to ensure the finite-time stability of the obtained sliding mode dynamics via an average dwell-time approach.